1988
DOI: 10.1063/1.341678
|View full text |Cite
|
Sign up to set email alerts
|

An electron paramagnetic resonance study of electron injected oxides in metal-oxide-semiconductor capacitors

Abstract: Electron paramagnetic resonance, in conjuction with electrical measurements, has been used to study Si-SiO2 interface defects produced as a result of negative bias, high-field electron injection into the SiO2 layer of metal-oxide-semiconductor capacitors. In particular, a search was made for Pb centers, previously identified as a source of interface traps in unannealed SiO2 on Si, and for E′ centers, which have been associated with trapped holes in SiO2. The results of the EPR experiments show no change in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Nevertheless, the possibility of interface trap generation where the defect atomic structure appears to be different from that of the P b -type center has been proposed by some researchers. 29,30 As far as nitrogen-containing dielectrics are concerned, EPR measurements have confirmed the existence of P b -type centres at Si-Si x N y and Si-SiO x N y interfaces. 31,32 Moreover, Fujieda et al 33 have inferred from a combination of conductance-frequency ͑G-͒, CV, and EPR measurements on a Si-SiO x N y interface undergoing NBTI that the P b -type centers are the dominant interface defects brought about by NBTI which was shown to occur mainly through the decomposition of P b -H pairs.…”
Section: Modelmentioning
confidence: 81%
“…Nevertheless, the possibility of interface trap generation where the defect atomic structure appears to be different from that of the P b -type center has been proposed by some researchers. 29,30 As far as nitrogen-containing dielectrics are concerned, EPR measurements have confirmed the existence of P b -type centres at Si-Si x N y and Si-SiO x N y interfaces. 31,32 Moreover, Fujieda et al 33 have inferred from a combination of conductance-frequency ͑G-͒, CV, and EPR measurements on a Si-SiO x N y interface undergoing NBTI that the P b -type centers are the dominant interface defects brought about by NBTI which was shown to occur mainly through the decomposition of P b -H pairs.…”
Section: Modelmentioning
confidence: 81%
“…On the other hand, more recently Warren et al have compared ESR measurements with C-V measurements, and found the number of trapped charges present was greater than the number of spins detected [ 171. Furthermore, Trombetta et al have generated APC's and observed no measurable ESR signal [18]. It seems clear that some of the trapped charge is in E' centers.…”
Section: Comparison With Other Experimentsmentioning
confidence: 98%
“…1-8 However, quantitative disagreements are common when comparing P b center data obtained from ESR and Si/ SiO 2 interface state data obtained from more conventional MOSFET electrical measurements. [9][10][11][12] For example, it's been argued that P b centers account for only a small fraction of electrically measured interface states with the remaining majority due to some unknown defect. 9,10 A potential source of the disagreements is the inability of most MOSFET electrical measurements to truly exclude the effects of noninterface defects, especially when dealing with samples of very poor quality.…”
Section: Spectroscopic Charge Pumping Investigation Of the Amphotericmentioning
confidence: 99%